The Effect of Person-Organization Fit and Job Satisfaction on the Organizational Commitment of Civil Servants in the Education and Culture Department of Melawi Regency - Agustista, Pirda; Arninda, Arninda (UNIVERSITAS PAKUAN, 2025)
This study analyzes the relationship between Person-Organization Fit and Job Satisfaction on Organizational Commitment among Civil Servants at the Education and Culture Office of Melawi Regency. The phenomenon of increased employee absenteeism and violations of office regulations reflects a low level of organizational commitment. The aim of this research is to identify factors influencing organizational commitment, with Person-Organization Fit and Job Satisfaction as independent variables. The method used is an associative study with data collection techniques through interviews and questionnaires. The respondents of this study are all civil servants, selected using a saturated sampling technique, totaling 46 participants. Data analysis was performed using multiple linear regression to determine the relationship between variables. The F-test results show that Person-Organization Fit and Job Satisfaction have a significant simultaneous effect on Organizational Commitment. The t-test results indicate that Person-Organization Fit has a positive and significant effect on Organizational Commitment, while Job Satisfaction does not have a significant effect on Organizational Commitment. The coefficient of determination shows that Person-Organization Fit and Job Satisfaction contribute 42% to Organizational Commitment, while the remaining percentage is influenced by other factors. This study recommends that employees should better understand the organizational culture and improve their commitment to their work. Furthermore, evaluating workloads and implementing transparent promotion processes can enhance employee motivation and commitment. Additionally, future research could expand by exploring other factors influencing organizational commitment and employing diverse research methodologies to provide more comprehensive insights.